1997
DOI: 10.2334/josnusd1959.39.133
|View full text |Cite
|
Sign up to set email alerts
|

Solubilizing efficiency of different gutta-percha solvents: A comparative study.

Abstract: Abstract:A study was conducted to comparatively evaluate the efficiency of different solvents for dissolving gutta-percha. Halothane, chloroform, xylene, acetone, isopropyl alcohol, turpentine, oil of mela-leuca and eucalyptol were used as solvents for dissolving standardized gutta-percha discs.Halothane, chloroform and xylene were markedly superior solvents of gutta-percha in comparison with the others. There was no significant difference among the three (p > 0.05). Eucalyptol, turpentine and oil of melaleuca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
0
18
0
4
Order By: Relevance
“…In the present study, xylol proved to be the most efficient. A comparative study of the dissolving efficiency of different solvents reported that xylol presents results similar to those of chloroform and halothane (15). Our results, however, showed that these two solvents were the least effective, perhaps due to their volatility.…”
Section: Discussionmentioning
confidence: 44%
“…In the present study, xylol proved to be the most efficient. A comparative study of the dissolving efficiency of different solvents reported that xylol presents results similar to those of chloroform and halothane (15). Our results, however, showed that these two solvents were the least effective, perhaps due to their volatility.…”
Section: Discussionmentioning
confidence: 44%
“…For example, chloroform and xylol have been shown to dissolve most root filling materials (Tamse et al. 1986, Wennberg & Orstavik 1989, Görduysus et al. 1997, Whitworth & Boursin 2000, Schäfer & Zandbiglari 2002, Magalhães et al.…”
Section: Introductionmentioning
confidence: 99%
“…com.br). doi:10.1111/j.1365-2591.2011.01912.x International Endodontic Journal, 44, 1024-1028, 2011 ª 2011 International Endodontic Journal xylol have been shown to dissolve most root filling materials (Tamse et al 1986, Wennberg & Orstavik 1989, Görduysus et al 1997, Whitworth & Boursin 2000, Schäfer & Zandbiglari 2002, Magalhães et al 2007), but it is reported to have carcinogenic potential and toxicity to tissues (Vajrabhaya et al 2004). Essential oils are able to dissolve most endodontic sealers and some, such as orange oil, eucalyptus oil and pine oil, have been reported to be safe and useful for this purpose (Hunter et al 1991, Uemura et al 1997, Hansen 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Por el contrario, el xileno está disponible actualmente para uso clínico, y no es considerado carcinogénico, aunque resulta ser muy tóxico para los tejidos. 3,13,18 La gutapercha también es soluble en aceites esenciales. Algunos de ellos han sido reportados como seguros y útiles para este propósito, por ejemplo, los aceites esenciales: eucalytus (eucalytol) y árbol de pino (turpentine) 14 .…”
Section: Introductionunclassified